Group training of narrative skills in French-speaking children with developmental language disorder. - Hadjadj, Olivia; Ardanouy, Estelle; Delage, Hélène (Child Language Teaching & Therapy, 2025)
Children with developmental language disorder (DLD) are known to present difficulties in storytelling, both in macrostructure (i.e., narrative scheme) and in microstructure (i.e., language complexity). Studies also show that children with DLD can improve their narrative macrostructural performance through specific intervention. While most intervention studies explore the impact of intervention on one type of narrative task in an individual setting, we explore the impact of intervention on two types of narrative tasks (story retelling and story generation) in a group setting. Children receive intervention on a story retelling task, and we examine whether they can generalize the narrative skills they have learned to a story generation task. Fifteen French-speaking children with DLD (aged 7;5 to 10;2) were trained into two groups of seven to eight children, during four to six sessions of 45 min each. Children had (1) to make the correspondence between an icon and a macrostructural element, (2) to learn macrostructure elements within a story, and (3) to practice the retelling of this story. In order to assess improvement between pre- and posttest, children were assessed via four baselines: two story retelling tasks (with only one story that was trained), one story generation, and a control measure (rapid automatized naming test). Children significantly improved on the three stories, in terms of the number of macrostructural elements learned. No improvement was observed on the control measure nor on the microstructural score. Our results confirmed that intervention focusing on macrostructure leads to improvement in this specific domain and that children with DLD can generalize learning acquired during a retelling task to a story generation one, a finding which has clinical applications for group intervention on narratives in speech–language therapy.